Engagement in dance is associated with emotional competence in interplay with others - Bojner Horwitz, Eva; Lennartsson, Anna-Karin; Theorell, Töres P. G.; Ullén, Fredrik (Frontiers in Psychology, 2015)
This study has explored the relation between dance achievement and alexithymia in a larger Swedish population sample (Swedish Twin Registry) with a study sample of 5431 individuals. Dance achievement (CAQ) was assessed in relation to Alexithymia (TAS-20) including the three subscales: Difficulty Identifying Feeling (DIF), Difficulty Describing Feeling (DDF) and Externally Oriented Thinking (EOT). The results show a significant negative association between the TAS subscale (EOT) and creative achievement in dance in female dancers compared to female and male non-dancers. A high EOT score corresponds to poor ability to communicate feelings to the environment. There was no observed association between the other factors DIF and DDF and dance achievement. Dance activity and training seem to be involved in the body´s emotional interplay with others. Embodied cognition, emotional perception and action are discussed as factors relevant to measuring in the skill of a dancer.